Peran Liberia dalam Mitigasi dan Proteksi Virus Ebola 2014-2016 - Akmal, Najwa Bilbina; Athaillah, Callista Diandra; Khairunnisa, Deanne Aurelia; Meilina, Udya Difa; Pasi, Lui Ardilo (Innovative: Journal Of Social Science Research, 2025)
The Ebola outbreak that hit West Africa in 2014 had a significant health and socio-economic impact on Liberia. As one of the hardest-hit countries, Liberia has learned much from this bitter experience. This article details Liberia's role in containing and defending against the Ebola virus, from the initial response to the outbreak to building a more resilient health system. Liberia has taken strategic steps to respond to the Ebola outbreak, including the establishment of rapid response teams, capacity building for health workers, and public education campaigns. In addition, Liberia is actively collaborating with international organisations and donor countries to address the outbreak. This article analyses the factors that influenced Liberia's success in containing the Ebola outbreak and the challenges it continues to face. We also discuss the lessons that can be learned from Liberia's experience to improve global preparedness for other infectious disease threats.